2022
DOI: 10.1021/jacs.2c12202
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Induces Its Own Preferred Heterochiral Host from Exclusive Homochiral Assembly

Abstract: Xenon binding represents a formidable challenge, and efficient hosts remain rare. Here we report our findings that while enantiomeric bis(urea)–bis(thiourea) macrocycles form exclusive homochiral dimeric assemblies, xenon is able to overcome the narcissism and induces an otherwise-nonobservable heterochiral assembly as its preferred host. An experimental approach and fitting model were developed to obtain binding constants associated with the invisible assembly species. The determined xenon binding affinity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The NH signals moved largely in the downfield direction even in this nonpolar solvent system, suggesting favorable hydrogen-bonding formation. The signal patterns are overall similar to that of the dimeric assembly (M S ) 2 or (M R ) 2 , except for higher complexity. By a combination of 1 H, 13 C, and various two-dimensional (2D) NMR experiments (Figures S4–S10), the two groups of signals can be assigned to the two kinds of dimeric assemblies MM -1 / PP -1 and MM -2 / PP -2 (Figure d).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…The NH signals moved largely in the downfield direction even in this nonpolar solvent system, suggesting favorable hydrogen-bonding formation. The signal patterns are overall similar to that of the dimeric assembly (M S ) 2 or (M R ) 2 , except for higher complexity. By a combination of 1 H, 13 C, and various two-dimensional (2D) NMR experiments (Figures S4–S10), the two groups of signals can be assigned to the two kinds of dimeric assemblies MM -1 / PP -1 and MM -2 / PP -2 (Figure d).…”
mentioning
confidence: 56%
“…This suggested that xenon induces the formation of an otherwise nonobservable heterochiral capsule MP/PM as its own preferred host, parallel to what was observed for the racemic mixture of M S and M R . 52 It seems that the global induced-fit assembly dynamics is universal for this type of bisurea− bisthiourea macrocycle system. The formation of up to six assembly products starting from a single macrocycle component represents an unprecedented example, highlighting the advantage of assembly diversity toward building complex matter.…”
mentioning
confidence: 99%
See 3 more Smart Citations